Comparative Statistical Analysis of Yield and Stability of Silver-Gold Nanoparticles Biosynthesized Using Different Reducing Agents - Kumar Mishra, Anand; Rodrick, Darshana (Journal of Neonatal Surgery, 2025)
Green synthesis of silver gold nanoparticles (AgAuNPs) using green reducing agents is a sustainable alternative to chemically synthesized nanoparticles with advantages of reducing biocompatibility and environmental safety. This work presents a comparative statistical analysis of AgAuNPs prepared using three biological reducing agents, viz, Moringa oleifera, Cinnamomum verum, and Fusarium oxysporum. Using correlation analysis, this research investigates the effect of reducing agents on nanoparticle yield, size, stability and SPR peak. Reducing agent type; nanoparticle yield; particle size; stability (zeta potential); and SPR peak were the five variables selected. The synthesis results exhibit a strong dependence on the choice of reducing agent. Plant based extracts also facilitated nanoparticle synthesis, whereas F. oxysporum, which is enzymatically active, yielded and was more stable on nanoparticles. However, the correlation matrix showed strong positive correlations of yield and stability, and inverse correlations of yield with size. This suggests that biological and process input optimization should be made to minimize particle production and ensure production stability. The study consequently promotes the development of green synthesis techniques and establishes statistical methodology for selecting appropriate reducers in nanoparticle biosynthesis.